History of the Literary Institutions in the Soviet Union and Beyond. An Introduction - Evgeny Dobrenko; Alessandro Farsetti (eSamizdat)
Introduction and preliminary remarks by the editors of the section “History of the Literary Institutions in the Soviet Union and Beyond”.